2014
DOI: 10.1002/chem.201404508
|View full text |Cite
|
Sign up to set email alerts
|

HOMO Stabilisation in π‐Extended Dibenzotetrathiafulvalene Derivatives for Their Application in Organic Field‐Effect Transistors

Abstract: Three new organic semiconductors, in which either two methoxy units are directly linked to a dibenzotetrathiafulvalene (DB-TTF) central core and a 2,1,3-chalcogendiazole is fused on the one side, or four methoxy groups are linked to the DB-TTF, have been synthesised as active materials for organic field-effect transistors (OFETs). Their electrochemical behaviour, electronic absorption and fluorescence emission as well as photoinduced intramolecular charge transfer were studied. The electron-withdrawing 2,1,3-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Despite all these studies, it should be kept in mind that the X‐ray diffraction patterns of the thin films revealed that the crystal structure of the films were in some cases differing from the single crystal structure, or that in some films, there was more than one coexisting phase. In other studies, similar findings related to the formation of crystal structures in thin films differing from the ones found in the resolved single crystal structures were reported . This highlights the complexity of controlling polymorphism, and the crucial importance of identifying the actual crystal structure of the processed semiconductor in the device to fully understand the relationship between structure and device performance.…”
Section: Tuning Crystal Structure and Polymorphismsupporting
confidence: 71%
See 1 more Smart Citation
“…Despite all these studies, it should be kept in mind that the X‐ray diffraction patterns of the thin films revealed that the crystal structure of the films were in some cases differing from the single crystal structure, or that in some films, there was more than one coexisting phase. In other studies, similar findings related to the formation of crystal structures in thin films differing from the ones found in the resolved single crystal structures were reported . This highlights the complexity of controlling polymorphism, and the crucial importance of identifying the actual crystal structure of the processed semiconductor in the device to fully understand the relationship between structure and device performance.…”
Section: Tuning Crystal Structure and Polymorphismsupporting
confidence: 71%
“…To overcome this, a few research groups have focused on synthesising DB‐TTF derivatives with electron‐withdrawing groups in order to shift down the HOMO levels. In this direction, electron deficient heterocycles such as imides and 2,1,3‐chalcongendiazole rings have been fused to the DB‐TTF core ( Figure a). The HOMO levels were lowered to values in the range from –5.1 to –5.3 eV, giving rise to devices that exhibited a high performance and, importantly, good ambient stability during several weeks.…”
Section: Electronic Modulationmentioning
confidence: 99%
“…Since the first demonstration of efficient organic light-emitting diodes (OLEDs) and organic photovoltaic (OPV) cells with the application of organic heterojunctions in the 1980s, , tremendous research effort has been devoted to synthesizing new materials and engineering interfacial properties to improve the efficiency of organic electronic devices. Over the years, it has been well-known that the energy level alignment and charge transfer (CT) states at the heterojunctions play crucial roles in controlling charge injection and exciton dissociation efficiencies. Particularly in OPVs, energy level alignment at the heterojunction has been the rule-of-thumb for designing new materials to improve the open-circuit voltage ( V OC ) in devices. Scharber et al have proposed that the V OC of the organic heterojunction photovoltaic cell is proportional to the energy difference between the highest-occupied molecular orbital ( E HOMO–D ) of the electron-donor material and the lowest-unoccupied molecular orbital ( E LUMO‑A ) of the electron–acceptor material, which has later been regarded as the effective energy gap ( E eff ) of organic heterojunctions . In most cases, the reported E eff is simply determined by assuming a common vacuum level alignment at the organic donor and acceptor interface.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, TTF-BTD­(Br) 2 behaves as a p-type semiconductor whereas TTF-BTD­(CN) 2 behaves as an ambipolar semiconductor . This great tunability in so many physical properties, when compared with other π-conjugated systems and coordination complexes, motivates the application of such fused D–A systems in the field of molecular electronics or nonlinear optics. ,, The study of their electronic tunability and charge-transfer characteristics is thus extremely valuable, and we recently carried out a study with Stark spectroscopy to elucidate the intimate link between the structural parameters and electronic features of the ground and excited states, such as polarizability and permanent dipoles . A question naturally arises: how does the tunability of the steady-state optical signals reflect on the dynamical properties of these systems?…”
Section: Introductionmentioning
confidence: 99%